2021
DOI: 10.3390/land10040341
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Urban Nature in Terms of Providing Ecosystem Services Related to Health and Well-Being: An Empirical Comparative Pilot Study of Cities in Germany and the Czech Republic

Abstract: The quality of life in our cities critically depends on the intelligent planning and shaping of urban living space, in particular urban nature. By providing a wide range of ecosystem services (ES), urban nature essentially contributes to the well-being of city dwellers and plays a major role in avoiding common diseases through its positive impact on physical and mental health. Health is one of the most important factors underlying human welfare and is, thus, vital to sustainable development. The ES of urban gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 30 publications
2
21
0
2
Order By: Relevance
“…Above this threshold, the sentiments of the residents were not significantly affected. In contrast, below 10%, as the percentage decreased, the sentiments of the residents improved substantially, which is in line with the planning and construction criteria of keeping neighborhoods away from industrial areas to improve their quality (33,34). When the migrant population in the neighborhood was <20%, the sentiments of the residents were largely unaffected and remained high.…”
Section: Non-linear Correlation Between Sentiments and The Built Envi...supporting
confidence: 57%
See 1 more Smart Citation
“…Above this threshold, the sentiments of the residents were not significantly affected. In contrast, below 10%, as the percentage decreased, the sentiments of the residents improved substantially, which is in line with the planning and construction criteria of keeping neighborhoods away from industrial areas to improve their quality (33,34). When the migrant population in the neighborhood was <20%, the sentiments of the residents were largely unaffected and remained high.…”
Section: Non-linear Correlation Between Sentiments and The Built Envi...supporting
confidence: 57%
“…( 1) Early studies focusing on land use have consistently shown that neighborhoods far away from industrial areas have better public health. Safety and welfare can promote a clean environment and improve the quality of life (33,34). A large amount of urban green space in neighborhoods can provide good air quality and landscape conditions to enhance sentiments (35-37).…”
Section: Literature Review Research On the Quantitative Analysis Of...mentioning
confidence: 99%
“…Finally, relevant studies of European and American cities have shown that racial and minority groups are key factors triggering differences in UGS allocations [ 32 , 82 , 83 , 84 ], whereas green space allocations in China are more influenced by specific factors such as natural endowments and major strategic planning. In addition to involving strategy and policy makers, UGS strategic planning requires public participation and monitoring since community residents are the direct beneficiaries of green spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Also, different types of response options to examine the intensity of preferences are applied as a part of data collection techniques. In order to understand what ES are the most important to well‐being, Likert scale questions or statements have been a vital part of preference elicitation studies (e.g., Syrbe et al, 2021; Tsantopoulos et al, 2018), as have multiple choice questions (e.g., Ferreira et al, 2021; Mara et al, 2020), ranking questions (e.g., Marques et al, 2020; Wilhelm et al, 2020), open‐ended questions (e.g., Landor‐Yamagata et al, 2018; Liu et al, 2017), numerical rating scale options (e.g., Mao et al, 2020; Williams et al, 2019), and dichotomous two‐point scale questions (e.g., Jericó‐Daminello et al, 2021). Likert scaling is used to measure preferences, and its standard format consists of a series of questions or statements for which the respondent is to indicate a degree of agreement or disagreement (Albaum, 1997).…”
Section: Methodological Backgroundmentioning
confidence: 99%